KNOWLEDGE MANAGEMENT PADA BANK SYARIAH, STUDI KASUS PADA BANK SYARIAH DI INDONESIA - Sri Wulandari (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2022)
Conventional banks have successfully implemented knowledge management strategies by using various models to support their business performance. Limited studies have been proposed on how Islamic Banks manage different knowledge to support their business processes. By using the knowledge management life cycle theory, the researcher studied the knowledge management process in several cases in Islamic banks in Indonesia. Researchers collected data by means of observation, written materials, and in-depth interviews with key informants from the Islamic bank. The results show that the knowledge management life cycle in Islamic banks does not always follow the theoretical model developed by previous research conducted in conventional banking organizations because Islamic banks have different characteristics. Islamic banks must integrate knowledge management into Islamic values and norms before they are stored, shared, used, and improved as shown in the theoretical model. This study explains and provides new insights about the knowledge management life cycle in Islamic banks both for academics and for practitioners.Â